Perfil e condições de trabalho dos profissionais do Programa Escola Integrada de Belo Horizonte - Camila Raquel Benevenuto de Andrade (2016)
This study had as a main goal trace the profile and professional working conditions operating in Programa Escola Integrada (PEI) - Integrated School Program, in the Municipal Educational System of Belo Horizonte (RME/BH), in the primary school stage. The program began in 2006 in seven municipal schools as a pilot project and is now part of the educational policy of the state capital. In research, we sought to verify the socio-economic profile, cultural and professional and working conditions that these professionals are submitted to. To answer these questions a quantitative survey was conducted. From the construction of a survey, the instrument used for the research was the questionnaire applied in thirty schools RME/BH. The subjects of the research were the professionals working in PEI at these 30 schools. Data were analyzed using the PSPP data analysis program. The framework was built based on the study of Integral Education policies; conceptions of comprehensive education in Brazil, the development of legislation on the extension of the school day, the academic debate on the inclusion of young professionals in schools, analysis of the Programa Escola Integrada, Plural School and finally a presentation of the data collected in the survey. Several authors have been mobilized for this study, highlighting: Rabbit (1997), Cavaliere (2002), Mauritius (2009), Moll (2011), Le Vasseur and Tardif (2009), Dayrell, et.al (2012), Macedo, et.al (2012). The results of this study showed that the PEI professionals are monitors and extension fellows, mostly women, brown, single, catholic, receive less than minimum wage, working 30 or 40 hours, have emotional relationship with students, teach workshops of Arts, Music and Body, Sports, Homework, Environment and Information Technology, have an average of 25 students in theirclasses. The working conditions are precarious, the places for holding the workshops are mostly adapted, tools and median wages are considered low.